Determinants of investment decisions on the capital market - Magdalena Jasiniak (e-Finanse: Financial Internet Quarterly, 2018)
The article deals with the psychological determinants of investment decisions made by an individual investor on the capital market. The purpose of this article is to try to assess the relationship between capital involvement and selected personality traits and how individuals perceive investments in securities of different nominal unit price. The author attempts to verify whether specific price thresholds affect respondents in a similar way as prices of goods and services to customers, in the context of capital investment. The results of the nationwide survey of 564 individual investors are based on analyses using the model of the willingness to invest in shares with a specific nominal value compared to the individual characteristics of the respondents. The results of the study indicate a significant relationship between personality traits and the tendency to choose stocks with relatively low or very high denomination (current transaction price).
Keywords: G11; G14; G41; 330; Behavioral finance; investment; capital market; investment psychology; denomination effect